Super-hydrophobic coating and preparation method thereof
By preparing a superhydrophobic coating of zinc-aluminum layered bimetallic hydroxide and Na2MoO4, combined with anion exchange method and hydrothermal method, the problem of limited single characteristics of existing coatings in strict environments is solved, and multiple functions are achieved. Anti-fouling, anti-icing and corrosion resistance.
Patent Information
- Application Number
- CN202411584132.3
- Authority / Receiving Office
- CN · China
- Patent Type
- Applications(China)
- Current Assignee / Owner
- Filing Date
- 2024-11-07
- Publication Date
- 2025-02-18
- Estimated Expiration
- 2044-11-07
AI Technical Summary
Existing superhydrophobic coatings usually have only single characteristics, limiting their application in harsh environments and cannot effectively prevent marine biofouling, anti-icing and corrosion resistance.
By preparing a superhydrophobic coating, the zinc-aluminum layered bimetallic hydroxide is mixed with Na2MoO4, and prepared by anion exchange method and hydrothermal method, combined with hydrophobic modification, it has anti-fouling, anti-freezing and corrosion resistance properties. coating.
It has achieved significant improvement in antifouling, anti-icing and corrosion resistance in harsh environments, and formed a superhydrophobic coating with multiple functions.
Smart Images

Figure CN119463626A_ABST
Abstract
Description
Technical Field
[0001] The invention belongs to the field of surface treatment, and particularly relates to a super-hydrophobic coating and a preparation method thereof. Background Art
[0002] The information disclosed in this background technology section is only intended to enhance the understanding of the overall background of the invention, and should not necessarily be regarded as an admission or any form of suggestion that the information constitutes the prior art already known to a person skilled in the art.
[0003] Marine biofouling and icing on equipment surfaces affect the performance and service life of marine equipment, increase operating and maintenance costs, and even cause casualties and economic losses. Therefore, they have always been two major problems that hinder human development and utilization of marine resources. To date, coating is the most economical and effective measure to prevent marine corrosion and biofouling. However, traditional polymer coatings have many defects, such as limited functionality, short service life, and poor durability. In recent years, super-hydrophobic functional materials have attracted attention due to their self-cleaning, anti-fouling and anti-corrosion properties, but they often only have a single characteristic, which limits the application of this material in harsh environments. Therefore, it is urgent to develop a super-hydrophobic coating with integrated anti-fouling, anti-icing and corrosion resistance properties. Summary of the invention
[0004] In order to solve the deficiencies of the prior art, an object of the present invention is to provide a super-hydrophobic coating and a preparation method thereof. The super-hydrophobic coating provided by the present invention has anti-fouling performance, anti-icing performance and corrosion resistance.
[0005] In order to achieve the above object, a first aspect of the present invention provides a method for preparing a super-hydrophobic coating, comprising:
[0006] 1) dissolving zinc and aluminum nitrates in water to obtain solution A, dissolving NaNO3 and NaOH in water to obtain solution B, mixing solution A and solution B, heating, stirring evenly, standing and aging to obtain a nitrate-intercalated zinc-aluminum layered double metal hydroxide;
[0007] 2) mixing the nitrate-intercalated zinc-aluminum layered double hydroxide with Na2MoO4 to prepare the zinc-aluminum layered double hydroxide by an anion exchange method;
[0008] 3) hydrophobically modifying the zinc-aluminum layered double metal hydroxide to obtain a modified zinc-aluminum layered double metal hydroxide;
[0009] 4) The modified zinc-aluminum layered double hydroxide is mixed with a polymer resin, a diluent, and a curing agent to obtain a super-hydrophobic coating material, and then cured to obtain a coating.
[0010] In some embodiments, the water is deionized water, distilled water or purified water.
[0011] In some embodiments, in step 1), the heating is heating to 45-85° C. and then keeping warm.
[0012] In some embodiments, in step 2), the nitrate-intercalated zinc-aluminum layered double metal hydroxide and Na2MoO4 are dissolved in water, stirred to react, and centrifuged to obtain a precipitate of zinc-aluminum layered double metal hydroxide;
[0013] In some embodiments, in step 3), the zinc-aluminum layered double hydroxide and stearate are dissolved in deionized water, stirred for reaction, and centrifuged to obtain a precipitate of hydrophobically modified zinc-aluminum layered double hydroxide.
[0014] In some embodiments, the zinc nitrate is Zn(NO3)2 or Zn(NO3)2·6H2O, the aluminum nitrate is Al(NO3)3 or Al(NO3)3·9H2O, and the Zn 2+ With Al 3+ The molar ratio is (1.5-2.5):1.
[0015] In some embodiments, the molar ratio of NaNO3 to NaOH is 2:(7-11).
[0016] In some embodiments, solution A and solution B are mixed in a ratio of (0.5-1.5):1.
[0017] In some embodiments, in step 1), solution A and solution B are mixed and then heated in an oil bath, the temperature of the oil bath is 55-75° C., the oil bath time is 14-34 h, and the aging time is 8-16 h.
[0018] In some embodiments, in step 2), the nitrate-intercalated zinc-aluminum layered double hydroxide and Na2MoO4 are dissolved in deionized water, stirred and aged under a nitrogen atmosphere to obtain a zinc-aluminum layered double hydroxide.
[0019] In some embodiments, nitrate-intercalated zinc-aluminum layered double hydroxide and Na2MoO4 are dissolved in deionized water at a mass ratio of (2-5):1.
[0020] In some embodiments, nitrate-intercalated zinc-aluminum layered double metal hydroxide and inorganic sodium salt are dissolved in deionized water to obtain a suspension, and the suspension is stirred in a 65-75° C. oil bath under a nitrogen atmosphere for 8-16 h and aged for 4-8 h to obtain zinc-aluminum layered double metal hydroxide.
[0021] In some embodiments, the stearate is one of sodium stearate and magnesium stearate, preferably sodium stearate.
[0022] In some embodiments, the mass ratio of zinc aluminum layered double hydroxide to sodium stearate is 1:(1-3); preferably 2:3.
[0023] In some embodiments, zinc-aluminum layered double hydroxide and stearate are dissolved in deionized water and kept at 80-120° C. for 6-10 hours to obtain a hydrophobically modified zinc-aluminum layered double hydroxide.
[0024] In some embodiments, the mass ratio of the hydrophobically modified zinc aluminum layered double hydroxide, the polymer resin, the diluent and the curing agent is (1-5):5:5:5.
[0025] In some embodiments, the polymer resin is any one of epoxy resin, polyurea resin, acrylic resin or polyurethane resin.
[0026] A second aspect of the present invention provides a super-hydrophobic coating obtained by the above-mentioned preparation method.
[0027] The beneficial effects of the present invention are:
[0028] 1. The super-hydrophobic coating material prepared by the present invention is sprayed on the surface of the substrate, and the double metal hydroxide nanoparticles therein shape a layer of micro-nano structure on the coating, so that the coating has a certain roughness, and can capture air at the solid-liquid interface to form a stable air film. Therefore, when water droplets fall on the surface of the coating, the contact area between the water droplets and the coating can be reduced to prevent corrosive ions from penetrating the coating. Secondly, the two-dimensional layered structure of the layered double metal hydroxide is a good physical barrier to prevent the diffusion of corrosive media, providing physical protection for the substrate.
[0029] 2. MoO4 loaded between the middle plates of the zinc-aluminum layered double hydroxide super hydrophobic coating material prepared by the present invention 2- or PO4 3- Can be released into the corrosive environment by ion exchange to intercept corrosive Cl - To the interlayer and provide corrosion inhibition. Therefore, the super-hydrophobic coating can effectively block H2O, O2 and Cl - It can resist the erosion of corrosive media and achieve excellent anti-fouling, anti-icing and corrosion resistance in harsh environments. BRIEF DESCRIPTION OF THE DRAWINGS
[0030] The accompanying drawings in the specification, which constitute a part of the present invention, are used to provide a further understanding of the present invention. The exemplary embodiments of the present invention and their descriptions are used to explain the present invention and do not constitute improper limitations on the present invention.
[0031] Figure 1 This is a flow chart of coating preparation according to Example 1 of the present invention;
[0032] Figure 2 are SEM images of different coatings of the present invention; wherein, (a) and (b) are SEM images of the LDH-MoO4 coating of Comparative Example 3 at different magnifications, and (c) and (d) are SEM images of the LDH-MoO4-St coating of Example 1 at different magnifications;
[0033] Figure 3 The figures are test results of the contact angles of carbon steel and different coatings of the present invention; wherein, (a) is the test result of the contact angle of the Q235 carbon steel surface, (b) is the test result of the contact angle of the EP coating of Comparative Example 4, (c) is the test result of the contact angle of the EP / LDH-MoO4 coating of Comparative Example 3, and (d) is the test result of the contact angle of the EP / LDH-MoO4-St coating of Example 1;
[0034] Figure 4 Figure 1 is a diagram of the antifouling test experimental process of the coating of Example 1 of the present invention and an optical photograph of droplets on the coating surface; wherein (a) is a rhodamine B solution, (b) is milk, (c) is orange juice, (d) is muddy water, (e) is a methyl blue solution, and (f) is an optical photograph of droplets on the coating surface;
[0035] Figure 5 The figures are the anti-icing test results of carbon steel and different coatings of the present invention; wherein (a) is Q235 carbon steel; (b) is the test result of the EP coating of comparative example 4, and (c) is the anti-icing test result of the coating of embodiment 1;
[0036] Figure 6 Impedance diagram, phase angle diagram, Nengquist diagram and equivalent circuit diagram of carbon steel of the present invention and different coatings of Example 1 and Comparative Example 4 Test data diagram of Q235 carbon steel and coatings of Comparative Example 3 and Comparative Example 4; wherein (a) is an impedance diagram, (b) is a phase angle diagram, and (c) is a Nengquist diagram;
[0037] Figure 7 This is a diagram of the superhydrophobic and anti-corrosion mechanism of the coating in Example 1 of the present invention. DETAILED DESCRIPTION
[0038] In view of the problem that existing super-hydrophobic coatings often have only a single characteristic, which limits the application scenarios of the coating, the present invention proposes a super-hydrophobic coating and a preparation method thereof.
[0039] In order to enable those skilled in the art to more clearly understand the technical solution of the present invention, the technical solution of the present invention will be described in detail below in conjunction with specific embodiments.
[0040] The materials used in the embodiments of the present invention are all common commercially available materials, wherein the epoxy resin is E51, the polyurea resin is SJKR 909H, the acrylic resin is PMMA, and the polyurethane resin is TPU.
[0041] Example 1
[0042] This embodiment provides a method for preparing a super hydrophobic coating, and the specific steps are as follows:
[0043] Dissolve Zn(NO3)2·6H2O (0.06 mol) and Al(NO3)3·9H2O (0.03 mol) in 100 mL of deionized water and place in a 500 mL beaker under stirring at room temperature to obtain a mixed solution A. Dissolve NaNO3 (0.04 mol) and NaOH (0.18 mol) in 100 mL of deionized water to form solution B. Mix solutions A and B in the beaker and heat in an oil bath at 65°C under stirring for 24 hours, age for 12 hours, then filter, cool to room temperature and transfer to a high-speed centrifuge, set the centrifugal speed to 6000 r / min, and the centrifugal time to 3 minutes. Wash the resulting precipitate once with anhydrous ethanol and then once with deionized water. Repeat the washing process three times. Finally, place it in a vacuum drying oven and place it at 80°C for 6 hours to obtain dry and pure ZnAl-LDH-NO3 - powder, denoted as LDH-NO3. - The powder is made into nanosheets for later use.
[0044] Preparation of ZnAl-LDH-MoO4 by anion exchange method 2- The preparation process of nanoparticles was carried out under nitrogen atmosphere. To avoid the contamination of nitrate anions, all solutions were prepared with boiled deionized water. Specifically, 2.4 g ZnAl-LDH-NO3 - The nanosheets were suspended in 100 mL of deionized water containing 1.2 g of Na2MoO4·2H2O. The suspension was vigorously stirred in a 70°C oil bath for 12 h and then aged for 6 h. It was then filtered, cooled to room temperature and transferred to a high-speed centrifuge at a centrifugal speed of 6000 r / min for 3 min. The resulting precipitate was washed once with anhydrous ethanol and then washed once with deionized water. The washing process was repeated three times. Finally, it was placed in a vacuum drying oven at 80°C for 6 h to obtain dry and pure ZnAl-LDH-MoO4 2- powder, denoted as LDH-MoO4.
[0045] Synthesis of superhydrophobic ZnAl-LDH-MoO4 by hydrothermal method 2- Nanoparticles, specifically: weigh 2g ZnAl-LDH-MoO4 2-The powder and 2g sodium stearate (St) were dissolved in 100mL deionized water solution. Then it was transferred to a polytetrafluoroethylene reactor, placed in an oven, and the temperature was adjusted to 100°C and kept warm for 8h. Then it was filtered, cooled to room temperature, and transferred to a high-speed centrifuge at a centrifugal speed of 6000r / min for 3min. The resulting precipitate was washed once with anhydrous ethanol and then washed once with deionized water. The washing process was repeated three times. Finally, it was placed in a vacuum drying oven at 80°C for 6h to obtain dry and pure ZnAl-LDH-MoO4 2- -St powder, denoted as LDH-MoO4-St.
[0046] A diluent was prepared by mixing xylene and ethylene glycol in a volume ratio of 7:3.
[0047] Weigh 3gLDH-MoO4-St powder, 5g epoxy resin E51 and 5g above-mentioned diluent mixing, at room temperature ultrasonic while stirring with glass rod until it is fully mixed. 5g8538 curing agent is subsequently added, ultrasonic simultaneously stirs 20min at room temperature to make it fully mixed. Coating is then put into vacuum drying oven, continues to pump 5min at room temperature to eliminate the bubble in coating, obtains super hydrophobic coating material.
[0048] Example 2
[0049] This embodiment provides a method for preparing a super hydrophobic coating, and the specific steps are as follows:
[0050] Dissolve Zn(NO3)2·6H2O (0.045 mol) and Al(NO3)3·9H2O (0.03 mol) in 100 mL of deionized water and place in a 500 mL beaker under stirring at room temperature to obtain a mixed solution A. Dissolve NaNO3 (0.04 mol) and NaOH (0.14 mol) in 100 mL of deionized water to form solution B. Mix 50 mL of solution A and 100 mL of solution B in the beaker and heat in an oil bath at 60°C for 20 h under stirring, age for 10 h, then filter, cool to room temperature and transfer to a high-speed centrifuge, set the centrifugal speed to 6000 r / min, and the centrifugal time to 3 min. Wash the resulting precipitate once with anhydrous ethanol and once with deionized water. Repeat the washing process three times. Finally, place it in a vacuum drying oven and place it at 80°C for 6 h to obtain dry and pure ZnAl-LDH-NO3 - powder, denoted as LDH-NO3. - The powder is made into nanosheets for later use.
[0051] ZnAl-LDH-MoO4 was prepared by anion exchange method. 2-The nanoparticles were prepared under nitrogen atmosphere. To avoid contamination by nitrate anions, all solutions were prepared with boiled deionized water. Specifically, 3.6 g ZnAl-LDH-NO3 - The nanosheets were suspended in 100 mL of deionized water containing 1.2 g of Na2MoO4·2H2O. The suspension was vigorously stirred in a 65°C oil bath for 8 h and then aged for 8 h. It was then filtered, cooled to room temperature and transferred to a high-speed centrifuge at a centrifugal speed of 6000 r / min for 3 min. The resulting precipitate was washed once with anhydrous ethanol and then washed once with deionized water. The washing process was repeated three times. Finally, it was placed in a vacuum drying oven at 80°C for 6 h to obtain dry and pure ZnAl-LDH-MoO4 2- powder, denoted as LDH-MoO4.
[0052] Synthesis of superhydrophobic ZnAl-LDH-MoO4 by hydrothermal method 2- Nanoparticles, specifically: weigh 2g ZnAl-LDH-MoO4 2- The powder and 4g sodium stearate (St) were dissolved in 100mL of deionized water solution. Then it was transferred to a polytetrafluoroethylene reactor, placed in an oven, and the temperature was adjusted to 80°C and kept warm for 10 hours. Then it was filtered, cooled to room temperature, and transferred to a high-speed centrifuge at a centrifugal speed of 6000r / min for 3 minutes. The resulting precipitate was washed once with anhydrous ethanol and then washed once with deionized water. The washing process was repeated three times. Finally, it was placed in a vacuum drying oven at 80°C for 6 hours to obtain dry and pure ZnAl-LDH-MoO4 2- -St powder, denoted as LDH-MoO4-St.
[0053] A diluent was prepared by mixing xylene and ethylene glycol in a volume ratio of 7:3.
[0054] Weigh 1gLDH-MoO4-St powder, 5g polyurea resin SJKR 909H and 5g above-mentioned diluent mixing, at room temperature ultrasonic while stirring with glass rod to its fully mixed uniform. 5g8538 curing agent is subsequently added, ultrasonic simultaneously stirs 20min at room temperature to make it fully mixed. Coating is then put into vacuum drying oven, continues to pump 5min at room temperature to eliminate the bubble in coating, obtains super hydrophobic coating material.
[0055] Example 3
[0056] This embodiment provides a method for preparing a super hydrophobic coating, and the specific steps are as follows:
[0057] Dissolve Zn(NO3)2·6H2O (0.075 mol) and Al(NO3)3·9H2O (0.03 mol) in 100 mL of deionized water and place in a 500 mL beaker under stirring at room temperature to obtain a mixed solution A. Dissolve NaNO3 (0.04 mol) and NaOH (0.22 mol) in 100 mL of deionized water to form solution B. Mix 100 mL of solution A and 67 mL of solution B in the beaker and heat in an oil bath at 45°C for 34 h under stirring, age for 16 h, then filter, cool to room temperature and transfer to a high-speed centrifuge, set the centrifugal speed to 6000 r / min, and the centrifugal time to 3 min. Wash the resulting precipitate once with anhydrous ethanol and once with deionized water. Repeat the washing process three times. Finally, place it in a vacuum drying oven and place it at 80°C for 6 h to obtain dry and pure ZnAl-LDH-NO3 - powder, denoted as LDH-NO3.
[0058] Preparation of ZnAl-LDH-MoO4 by anion exchange method 2- Nanoparticles, specifically: The preparation process was carried out under nitrogen atmosphere. In order to avoid contamination by nitrate anions, all solutions were prepared with boiled deionized water. Specifically: 4.8 g ZnAl-LDH-NO3 - The nanosheets were suspended in 100 mL of deionized water containing 1.2 g of Na2MoO4·2H2O. The suspension was vigorously stirred in a 75°C oil bath for 8 h and then aged for 4 h. It was then filtered, cooled to room temperature and transferred to a high-speed centrifuge at a centrifugal speed of 6000 r / min for 3 min. The resulting precipitate was washed once with anhydrous ethanol and then washed once with deionized water. The washing process was repeated three times. Finally, it was placed in a vacuum drying oven at 80°C for 6 h to obtain dry and pure ZnAl-LDH-MoO4 2- powder, denoted as LDH-MoO4. ZnAl-LDH-NO3 - The powder is made into nanosheets for later use.
[0059] Synthesis of superhydrophobic ZnAl-LDH-MoO4 by hydrothermal method 2- Nanoparticles, specifically: weigh 2g ZnAl-LDH-MoO4 2-The powder and 6g sodium magnesium stearate (St) were dissolved in 100mL of deionized water solution. Then it was transferred to a polytetrafluoroethylene reactor, placed in an oven, and the temperature was adjusted to 120°C and kept warm for 6h. Then it was filtered, cooled to room temperature, and transferred to a high-speed centrifuge with a centrifugal speed of 6000r / min and a centrifugal time of 3min. The resulting precipitate was first washed once with anhydrous ethanol and then washed once with deionized water. The washing process was repeated three times. Finally, it was placed in a vacuum drying oven and placed at 80°C for 6h to obtain dry and pure ZnAl-LDH-MoO4 2- -St powder, denoted as LDH-MoO4-St.
[0060] A diluent was prepared by mixing xylene and ethylene glycol in a volume ratio of 7:3.
[0061] Weigh 5gLDH-MoO4-St powder, 5g acrylic resin PMMA and 5g above-mentioned diluent mixing, at room temperature ultrasonic while stirring with glass rod until it is fully mixed. 5g8538 curing agent is subsequently added, ultrasonic simultaneously stirs 20min at room temperature to make it fully mixed. Coating is then put into vacuum drying oven, continues to pump 5min at room temperature to eliminate the bubble in coating, obtains super hydrophobic coating material.
[0062] Example 4
[0063] This embodiment provides a method for preparing a super hydrophobic coating, and the specific steps are as follows:
[0064] Dissolve Zn(NO3)2·6H2O (0.06 mol) and Al(NO3)3·9H2O (0.03 mol) in 100 mL of deionized water and place in a 500 mL beaker under stirring at room temperature to obtain a mixed solution A. Dissolve NaNO3 (0.04 mol) and NaOH (0.18 mol) in 100 mL of deionized water to form solution B. Mix solutions A and B in the beaker and heat in an oil bath at 85°C for 14 h under stirring, age for 8 h, then filter, cool to room temperature and transfer to a high-speed centrifuge, set the centrifugal speed to 6000 r / min, and the centrifugal time to 3 min. Wash the precipitate once with anhydrous ethanol and then with deionized water. Repeat the washing process three times. Finally, place it in a vacuum drying oven and place it at 80°C for 6 h to obtain dry and pure ZnAl-LDH-NO3 - powder, denoted as LDH-NO3. - The powder is made into nanosheets for later use.
[0065] Preparation of ZnAl-LDH-MoO4 by anion exchange method 2-The preparation process of nanoparticles was carried out under nitrogen atmosphere. To avoid the contamination of nitrate anions, all solutions were prepared with boiled deionized water. Specifically, 2.4 g ZnAl-LDH-NO3 - The nanosheets were suspended in 100 mL of deionized water containing 1.2 g of Na2MoO4·2H2O. The suspension was vigorously stirred in a 70°C oil bath for 12 h and then aged for 6 h. It was then filtered, cooled to room temperature and transferred to a high-speed centrifuge at a centrifugal speed of 6000 r / min for 3 min. The resulting precipitate was washed once with anhydrous ethanol and then washed once with deionized water. The washing process was repeated three times. Finally, it was placed in a vacuum drying oven at 80°C for 6 h to obtain dry and pure ZnAl-LDH-MoO4 2- powder, denoted as LDH-MoO4.
[0066] Synthesis of superhydrophobic ZnAl-LDH-MoO4 by hydrothermal method 2- Nanoparticles, specifically: weigh 2g ZnAl-LDH-MoO4 2- The powder and 2g of magnesium stearate were dissolved in 100mL of deionized water solution. Then it was transferred to a polytetrafluoroethylene reactor, placed in an oven, and the temperature was adjusted to 100°C and kept warm for 8h. Then it was filtered, cooled to room temperature, and transferred to a high-speed centrifuge at a centrifugal speed of 6000r / min for 3min. The resulting precipitate was washed once with anhydrous ethanol and then washed once with deionized water. The washing process was repeated three times. Finally, it was placed in a vacuum drying oven at 80°C for 6h to obtain dry and pure ZnAl-LDH-MoO4 2- -St powder, denoted as LDH-MoO4-St.
[0067] A diluent was prepared by mixing xylene and ethylene glycol in a volume ratio of 7:3.
[0068] Weigh 3gLDH-MoO4-St powder, 5g polyurethane resin TPU and 5g rare above-mentioned diluent mixing, at room temperature ultrasonic while stirring with glass rod until it is fully mixed. 5g8538 curing agent is subsequently added, ultrasonic simultaneously stirs 20min at room temperature to make it fully mixed. Coating is then put into vacuum drying oven, continues to pump 5min at room temperature to eliminate the bubble in coating, obtains super hydrophobic coating material.
[0069] Comparative Example 1
[0070] Dissolve Zn(NO3)2·6H2O (0.06 mol) and Al(NO3)3·9H2O (0.03 mol) in 100 mL of deionized water and place in a 500 mL beaker under stirring at room temperature to obtain a mixed solution A. Dissolve NaNO3 (0.04 mol) and NaOH (0.18 mol) in 100 mL of deionized water to form solution B. Mix solutions A and B in the beaker and heat in an oil bath at 65°C under stirring for 24 hours, age for 12 hours, then filter, cool to room temperature and transfer to a high-speed centrifuge, set the centrifugal speed to 6000 r / min, and the centrifugal time to 3 minutes. Wash the resulting precipitate once with anhydrous ethanol and then once with deionized water. Repeat the washing process three times. Finally, place it in a vacuum drying oven and place it at 80°C for 6 hours to obtain dry and pure ZnAl-LDH-NO3 - powder, denoted as LDH-NO3.
[0071] Dissolve 1g LDH-NO3 powder and 1.53g sodium stearate (St) in 100mL deionized water solution. Then transfer to a polytetrafluoroethylene reactor, put it in an oven, adjust the temperature to 100℃ and keep it warm for 8h. Then filter, cool to room temperature and transfer to a high-speed centrifuge with a centrifugal speed of 6000r / min and a centrifugal time of 3min. The resulting precipitate is first washed once with anhydrous ethanol and then washed once with deionized water. The washing process is repeated three times. Finally, put it in a vacuum drying oven and place it at 80℃ for 6h to obtain dry and pure ZnAl-LDH-NO3 - -St powder. ZnAl-LDH-NO3 - -St powder is made into nanosheets for later use.
[0072] Prepare ZnAl-LDH-NO3 - -St nanosheets were dissolved in 5 mL of deionized water (0.5 wt.%) and ultrasonically treated for 5 min, then each nanosheet was added to 50 g of epoxy resin E51 and stirred for 20 min with a strong stirrer at room temperature, and then 15 g of 8538 curing agent was added to the EP / LDH mixture and stirred for 10 min to fully mix it, which was recorded as EP / LDH-NO3-St. The coating was then placed in a vacuum drying oven and continuously evacuated for 5 min at room temperature to eliminate bubbles in the coating to obtain a superhydrophobic coating material.
[0073] Comparative Example 2
[0074] Dissolve Zn(NO3)2·6H2O (0.06 mol) and Al(NO3)3·9H2O (0.03 mol) in 100 mL of deionized water and place in a 500 mL beaker under stirring at room temperature to obtain a mixed solution A. Dissolve NaNO3 (0.04 mol) and NaOH (0.18 mol) in 100 mL of deionized water to form solution B. Mix solutions A and B in the beaker and heat in an oil bath at 65°C under stirring for 24 hours, age for 12 hours, then filter, cool to room temperature and transfer to a high-speed centrifuge, set the centrifugal speed to 6000 r / min, and the centrifugal time to 3 minutes. Wash the resulting precipitate once with anhydrous ethanol and then once with deionized water. Repeat the washing process three times. Finally, place it in a vacuum drying oven and place it at 80°C for 6 hours to obtain dry and pure ZnAl-LDH-NO3 - powder, denoted as LDH-NO3.
[0075] Dissolve Na3PO4·12H2O (0.2 mol) in 500 mL of deionized water. Then add 0.5 g ZnAl-LDH-NO3 - Dispersed in the solution, stirred at room temperature for 48 hours, then filtered, cooled to room temperature and transferred to a high-speed centrifuge, the centrifugal speed was 6000r / min, the centrifugal time was 3min, the obtained precipitate was first washed once with anhydrous ethanol, then washed once with deionized water, and the washing process was repeated three times. Finally, it was placed in a vacuum drying oven at 80℃ for 6 hours to obtain dry and pure ZnAl-LDH-PO4 3- Powder, denoted as LDH-PO4.
[0076] Dissolve 1g LDH-PO4 powder and 1.53g sodium stearate (St) in 100mL deionized water solution. Then transfer to a polytetrafluoroethylene reactor, put it in an oven, adjust the temperature to 100°C and keep it warm for 8h. Then filter, cool to room temperature and transfer to a high-speed centrifuge with a centrifugal speed of 6000r / min and a centrifugal time of 3min. The resulting precipitate is first washed once with anhydrous ethanol and then washed once with deionized water. The washing process is repeated three times. Finally, put it in a vacuum drying oven and place it at 80°C for 6h to obtain dry and pure ZnAl-LDH-PO4 3- -St powder. ZnAl-LDH-PO4 3- -St powder is made into nanosheets for later use.
[0077] The prepared ZnAl-LDH-PO4 3--St nanosheets were dissolved in 5 mL of deionized water (0.5 wt.%) and ultrasonically treated for 5 min, then each nanosheet was added to 50 g of epoxy resin E51 and stirred with a strong stirrer at room temperature for 20 min, and then 15 g of 8538 curing agent was added to the EP / LDH mixture and stirred for 10 min to fully mix it. The coating was then placed in a vacuum drying oven and continuously evacuated for 5 min at room temperature to eliminate bubbles in the coating to obtain a super hydrophobic coating material.
[0078] Comparative Example 3
[0079] Dissolve Zn(NO3)2·6H2O (0.06 mol) and Al(NO3)3·9H2O (0.03 mol) in 100 mL of deionized water and place in a 500 mL beaker under stirring at room temperature to obtain a mixed solution A. Dissolve NaNO3 (0.04 mol) and NaOH (0.18 mol) in 100 mL of deionized water to form solution B. Mix solutions A and B in the beaker and heat in an oil bath at 65°C under stirring for 24 hours, age for 12 hours, then filter, cool to room temperature and transfer to a high-speed centrifuge, set the centrifugal speed to 6000 r / min, and the centrifugal time to 3 minutes. Wash the resulting precipitate once with anhydrous ethanol and then once with deionized water. Repeat the washing process three times. Finally, place it in a vacuum drying oven and place it at 80°C for 6 hours to obtain dry and pure ZnAl-LDH-NO3 - powder, denoted as LDH-NO3. - The powder is made into nanosheets for later use.
[0080] Preparation of ZnAl-LDH-MoO4 by anion exchange method 2- The preparation process of nanoparticles was carried out under nitrogen atmosphere. To avoid the contamination of nitrate anions, all solutions were prepared with boiled deionized water. Specifically, 2.5 g ZnAl-LDH-NO3 - The nanosheets were suspended in 100 mL of deionized water containing 1.2 g of Na2MoO4·2H2O. The suspension was vigorously stirred in a 70°C oil bath for 12 h and then aged for 6 h. It was then filtered, cooled to room temperature and transferred to a high-speed centrifuge at a centrifugal speed of 6000 r / min for 3 min. The resulting precipitate was washed once with anhydrous ethanol and then washed once with deionized water. The washing process was repeated three times. Finally, it was placed in a vacuum drying oven at 80°C for 6 h to obtain dry and pure ZnAl-LDH-MoO4 2- powder, denoted as LDH-MoO4.
[0081] A diluent was prepared by mixing xylene and ethylene glycol in a volume ratio of 7:3.
[0082] Weigh 3gLDH-MoO4 powder, 5gEP and 5g above-mentioned diluent are mixed, and stirred with glass rod until it is fully mixed at room temperature while being ultrasonic. 5g8538 curing agent is subsequently added, and ultrasonic stirring is simultaneously carried out at room temperature for 20min to make it fully mixed. Coating is then put into vacuum drying oven, and air is continuously pumped for 5min at room temperature to eliminate the bubble in coating, and super-hydrophobic coating material is obtained.
[0083] Comparative Example 4
[0084] 5 g of EP was weighed and mixed with 5 g of the diluent of Example 1, and stirred with a glass rod at room temperature while ultrasonic treatment until they were fully mixed. Then 5 g of 8538 curing agent was added, and ultrasonic treatment was performed at room temperature while stirring for 20 min to fully mix them. Then the coating was placed in a vacuum drying oven, and the air was continuously pumped for 5 min at room temperature to eliminate bubbles in the coating, thereby obtaining a coating material.
[0085] Experimental example
[0086] The Q235 carbon steel was polished and leveled with 220-mesh and 600-mesh sandpapers respectively, and then degreased by washing with acetone in an ultrasonic cleaner for 10 minutes. Then, it was ultrasonically cleaned with anhydrous ethanol for 10 minutes and then with deionized water for 10 minutes. This process was to remove surface impurities. After cleaning, it was placed in a vacuum drying oven for drying.
[0087] The coating materials of the above-mentioned embodiment and comparative example were loaded into the spray gun cavity respectively, and the coating was sprayed on different substrate surfaces with an air pressure of 50 kPa, and the spraying distance was 20 cm. After spraying, it was placed in a vacuum drying oven at 60°C for 3 hours to ensure rapid pre-curing of the coating, and then cured at room temperature for 48 hours to obtain a fully cured coating.
[0088] The coating obtained above was inspected, and its antifouling performance, anti-icing performance and corrosion resistance were tested.
[0089] The corrosion resistance is tested by a neutral salt spray test method: the temperature of the test box should be controlled at (35±2)°C, the humidity is greater than 95%, the concentration of the sodium chloride solution is 5%±0.5%, the pH value is 6.5-7.2, and the coating is made with an artificial scratch with a width of 0.5 mm to observe the degree of corrosion at the scratch. Here, the coatings prepared by the coating materials of Example 1 and Comparative Examples 1-3 are taken as examples to compare their corrosion resistance.
[0090] Neutral salt spray test data
[0091] Exposure time 100h 300h 500h Example 1 Slight corrosion Slight corrosion Slight pitting Comparative Example 1 Slight pitting Severe pitting Slight peeling Comparative Example 2 Slight corrosion Severe corrosion Severe pitting Comparative Example 3 Slight corrosion Severe corrosion Severe pitting
[0092] Comparative Example 1 did not undergo anion exchange, and the coating exhibited poor anti-corrosion performance, especially after 300 hours, large-sized block corrosion products were formed, and pitting was serious. Comparative Example 2 used sodium phosphate, and Comparative Example 3 was not modified. Both coatings formed block corrosion products after 500 hours. Example 1 exhibited the least corrosion products, and only slight pitting occurred at 500 hours, which was significantly better than Comparative Examples 1-3, showing superior anti-corrosion performance.
[0093] Figure 3 The test results of the contact angle of Q235 steel, comparative example 4, comparative example 3 and embodiment 1 are shown in FIG. Figure 3 It can be seen in a that the contact angle of the Q235 carbon steel surface after sandpaper pretreatment is about 61.5±0.5°, indicating the hydrophilicity of the substrate surface. Figure 3 (b) shows the surface contact angle of the pure epoxy coating prepared on the Q235 carbon steel surface. Compared with the bare carbon steel substrate surface, its contact angle increased to 76.8±0.5°, which is still hydrophilic. The contact angle of the EP / LDH-MoO4 coating surface formed by the unmodified LDH-MoO4 nanoparticles and the epoxy coating was further increased to 90.2±0.5°, as shown in Figure 2. Figure 3 (c) is only a hydrophobic surface. However, the contact angle of the EP / LDH-MoO4-St coating surface prepared by spraying the nanoparticles modified with sodium stearate reached 156.3±0.5°, which is a super hydrophobic surface. Figure 3 (d) This is because the LDH-MoO4 nanoparticles were modified by introducing sodium stearate, a low surface material, to prepare super-hydrophobic LDH-MoO4-St nanoparticles, which shaped a certain surface roughness in the composite coating, and cavitation was generated in the surface depressions, thereby forming an air film between the liquid and the solid, which reduced the contact area between the water droplets and the coating, showing super-hydrophobic properties.
[0094] Figure 4 To test the antifouling performance of the coating in Example 1, the method of immersing in dye wastewater was adopted for research. The experimental liquids were rhodamine b solution, milk, orange juice, muddy water, and methyl blue solution (0.5g of the corresponding test powder was dissolved in 30ml of deionized water and stirred evenly). These different liquids were placed in a white plastic cup. The sample coated with EP / LDH-MoO4-St coating was clamped with tweezers, and then immersed in different dye liquids for 1 minute and then taken out. From the initial immersion of the carbon steel sample coated with EP / LDH-MoO4-St coating in dye wastewater to the subsequent removal of the sample, no residual pollution was observed on the sample surface. The low adhesion between the EP / LDH-MoO4-St coating and the pollutant and the low sliding angle on the coating surface contribute to the good antifouling performance of the coating surface.
[0095] Figure 5 The results of the anti-icing test of the coatings in Q235 steel, comparative example 4 and example 1 are shown. On the Q235 steel substrate, it can be clearly observed that the water droplets begin to freeze at 45 seconds and completely freeze at 75 seconds. On the surface of the EP / LDH-MoO4 coating, Figure 5 As shown in (b), the water droplet begins to freeze at 70 seconds and is completely frozen at 157 seconds. Figure 5 As shown in (c), the water droplet on the EP / LDH-MoO4-St coating surface began to freeze at 195 seconds and was completely frozen at 340 seconds, indicating that the superhydrophobic coating surface can significantly delay the freezing process.
[0096] Figure 6 The electrochemical performance test results of the coatings in Q235 steel, comparative example 4, comparative example 3 and embodiment 1 are shown in Figure 2. In the coating system, it is generally believed that high impedance values in the low frequency region and higher phase angles in the high frequency region indicate better corrosion resistance. Q235 carbon steel has the lowest impedance value (2.53×10 3 Ω·cm 2 ). The Q235 carbon steel coated with EP coating makes use of the physical barrier properties of EP to make the overall impedance modulus (Z f =0.01Hz) is about 2 orders of magnitude higher than that of bare Q235 carbon steel, reaching 7.29×10 5 Ω·cm 2 For Q235 carbon steel coated with EP / LDH-MoO4, the physical barrier effect and active ion exchange of LDH-MoO4 itself improve the corrosion resistance of the composite coating, making its impedance value (Z f =0.01Hz) reaches 7.84×10 7 Ω·cm 2 For Q235 carbon steel coated with EP / LDH-MoO4-St super-hydrophobic coating, its impedance (Z f =0.01Hz) value is further increased to 1.35×10 11 Ω·cm 2 , showing better corrosion resistance.
[0097] In addition, the phase angle of the high frequency region in the Bode diagram is also a key parameter for evaluating the corrosion resistance of the coating. Figure 6It can be seen from (b) that the phase angle of bare Q235 carbon steel does not have the curve trend of a typical coating, and an obvious peak appears in the mid-frequency region, which indicates that the bare Q235 carbon steel has undergone relatively serious corrosion in 3.5wt.% NaCl solution. Compared with other coated samples that did not produce corrosion, solution resistance was generated during the corrosion process of the bare Q235 carbon steel. After coating with different coatings, the phase angle trends of the three sample coatings are generally consistent. It can be clearly seen from the figure that all coated samples have a relatively wide platform in the high-frequency region. More importantly, the Q235 carbon steel coated with the EP / LDH-MoO4-St superhydrophobic coating has the highest phase angle value and the widest platform area, proving its best anti-penetration performance. Figure 6 As shown in (c), the Nyquist plot shows the difference in corrosion resistance of different coatings. Generally speaking, the larger the diameter of the capacitance-inductive arc in the Nyquist plot, the stronger the anti-permeability performance. Among them, the capacitance arc of bare Q235 carbon steel is the smallest, while the capacitance arc diameter of Q235 carbon steel coated with EP / LDH-MoO4-St superhydrophobic coating is the largest. These results are consistent with the previous analysis, further proving the excellent anti-permeability performance of EP / LDH-MoO4-St superhydrophobic coating.
[0098] Figure 7 The diagram shows the super-hydrophobic and anti-corrosion mechanism of the EP / LDH-MoO4-St coating in Example 1. First, the super-hydrophobic EP / LDH-MoO4-St nanoparticles create a layer of micro-nano structure on the coating, which gives the coating a certain degree of roughness and can capture air at the solid-liquid interface to form a stable air film. Therefore, when water droplets fall on the surface of the coating, the contact area between the water droplets and the coating can be reduced to prevent corrosive ions from penetrating the coating. Secondly, the two-dimensional layered structure of LDH is a good physical barrier to prevent the diffusion of corrosive media and provide physical protection for the substrate. In addition, the MoO42- loaded between the layers of LDH-MoO4 can be released into the corrosive environment by means of ion exchange to intercept corrosive Cl - to the interlayer and provide corrosion inhibition. Therefore, the EP / LDH-MoO4-St superhydrophobic coating can effectively block H2O, O2 and Cl - It can resist the erosion of corrosive media and achieve excellent anti-fouling, anti-icing and corrosion resistance in harsh environments.
[0099] The above tests are only described with some embodiments and comparative examples, and other embodiments also have the same or similar effects. The technical solution of the present invention has excellent anti-fouling performance, anti-icing performance and corrosion resistance, and achieves very excellent protection performance in harsh environments.
[0100] The above description is only a preferred embodiment of the present invention and is not intended to limit the present invention. For those skilled in the art, the present invention may have various modifications and variations. Any modification, equivalent replacement, improvement, etc. made within the spirit and principle of the present invention shall be included in the protection scope of the present invention.
Claims
1. A method for preparing a super hydrophobic coating, characterized in that, include: 1) dissolving zinc and aluminum nitrates in water to obtain solution A, dissolving NaNO3 and NaOH in water to obtain solution B, mixing solution A and solution B, heating, stirring evenly, standing and aging to obtain a nitrate-intercalated zinc-aluminum layered double metal hydroxide; 2) mixing the nitrate-intercalated zinc-aluminum layered double hydroxide with Na2MoO4 to prepare the zinc-aluminum layered double hydroxide by an anion exchange method; 3) hydrophobically modifying the zinc-aluminum layered double metal hydroxide to obtain a modified zinc-aluminum layered double metal hydroxide; 4) The modified zinc-aluminum layered double hydroxide is mixed with a polymer resin, a diluent, and a curing agent to obtain a super-hydrophobic coating material, and then cured to obtain a coating.
2. The method for preparing a super hydrophobic coating according to claim 1, wherein In step 1), the heating is heating to 45-85° C. and then keeping warm; Or, in step 2), the nitrate-intercalated zinc-aluminum layered double metal hydroxide and Na2MoO4 are dissolved in water, stirred to react, and centrifuged to obtain a precipitate of zinc-aluminum layered double metal hydroxide; Or, in step 3), the zinc-aluminum layered double metal hydroxide and stearate are dissolved in deionized water, stirred for reaction, and centrifuged to obtain a precipitate of hydrophobically modified zinc-aluminum layered double metal hydroxide.
3. The preparation method of super hydrophobic coating as claimed in claim 1, characterized in that, The zinc nitrate is Zn(NO3)2 or Zn(NO3)2·6H2O, the aluminum nitrate is Al(NO3)3 or Al(NO3)3·9H2O, and the Zn 2+ With Al 3+ The molar ratio is (1.5-2.5):1; Or, the molar ratio of NaNO3 to NaOH is 2:(7-11); Alternatively, solution A and solution B are mixed in a ratio of (0.5-1.5):
1.
4. The method for preparing a super hydrophobic coating according to claim 1, wherein In step 1), solution A and solution B are mixed and then heated in an oil bath, the temperature of the oil bath is 55-75° C., the oil bath time is 14-34 hours, and the aging time is 8-16 hours.
5. The method for preparing a super hydrophobic coating according to claim 1, wherein In step 2), the nitrate-intercalated zinc-aluminum layered double hydroxide and Na2MoO4 are dissolved in deionized water, stirred and aged under a nitrogen atmosphere to obtain a zinc-aluminum layered double hydroxide; preferably, the nitrate-intercalated zinc-aluminum layered double hydroxide and Na2MoO4 are dissolved in deionized water in a mass ratio of (2 to 5):
1.
6. The method for preparing a super hydrophobic coating according to claim 1, wherein The stearate is one of sodium stearate and magnesium stearate, preferably sodium stearate.
7. The method for preparing a super hydrophobic coating according to claim 6, wherein The mass ratio of zinc-aluminum layered double hydroxide to sodium stearate is 1:(1-3); preferably 2:
3.
8. The method for preparing a super hydrophobic coating according to claim 1, wherein The zinc-aluminum layered double metal hydroxide and stearate are dissolved in deionized water and kept at 80-120° C. for 6-10 hours to obtain a hydrophobically modified zinc-aluminum layered double metal hydroxide.
9. The method for preparing a super hydrophobic coating according to claim 1, wherein The polymer resin is one of epoxy resin, polyurea resin, acrylic resin or polyurethane resin.
10. A super hydrophobic coating, characterized in that: The method is obtained by the preparation method according to any one of claims 1 to 9.
Citation Information
Patent Citations
Preparation method of bionic super-lubricating composite anti-corrosion coating with self-restoration function
CN111593393A
Method for preparing super-hydrophobic zinc-aluminum hydrotalcite coating on surface of aluminum alloy
CN112359356A
Corrosion-resistant super-hydrophobic layered double hydroxide coating for aluminum alloy surface and preparation method and application thereof
CN113318946A
Corrosion-inhibition anion intercalation layered double-metal hydroxide and preparation method and application thereof
CN113716574A
Construction method of super-hydrophobic self-healing anticorrosive coating with corrosion inhibition function
CN115156010A